The role of sport participation and body mass index in predicting motor competence of school-age children - Luciana Ferreira; Jose Luiz Lopes Vieira; Raquel Nichele de Chaves; Romulo Araújo Fernandez; Pamela Norraila da Silva; Francielle Rocha; Francielle Cheuczuk; Priscila Caçola (Revista da Educação Física)
Purpose: Our goal was to investigate the association between sport participation (SP) and motor competence (MC), and to assess the mediation role of body mass index (BMI) on this association. Method: 707 children (332 boys, 375 girls) aged between 6- to 10 years participated in the study. MC was assessed using the BOT-2. Parents were asked about organized SP, and BMI was calculated based on the child’s height and weight. Results: Our findings showed that SP was associated with MC, and BMI was not an important factor in these relationships. However, a small mediation of BMI was found, but only for obese children. Conclusion: In summary, that sport participation plays a relevant role in the development of motor competence in school-age children, and that association is, in general, not mediated by weight status.